2016
DOI: 10.1016/j.vetpar.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of goats against Haemonchus contortus with the gut membrane proteins H11/H-gal-GP

Abstract: Forty goats, aged from 2 to 5 months were subjected to two different immunization protocols with a vaccine containing Haemonchus contortus gut membrane proteins H11/H-gal-GP to evaluate protection against H. contortus on pre-contaminated pastures. Goats were allocated to four groups of ten, three of them received their first vaccination before turnout. One group (V4) was then vaccinated at 4-week-intervals whereas another two groups (V6 and V6SEP) were vaccinated at 6-week-intervals. A control group (CTRL) rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
12
0
3
Order By: Relevance
“…In this research, goats immunized with rHcftt2 showed a significant 26.46% reduction in egg output, and the same vaccinated animals displayed a 32.22% reduction in the amount of adult H. contortus collected from the abomasa compared with the positive control group at the end of the trial. The female adult reduction was higher than the male reduction, most likely indicating the higher blood intake of the female worms [8]. Unfortunately, the reductions of adult worms were not statistically significant, probably due to the presence of nonresponsive animals in each group and the sampling size.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this research, goats immunized with rHcftt2 showed a significant 26.46% reduction in egg output, and the same vaccinated animals displayed a 32.22% reduction in the amount of adult H. contortus collected from the abomasa compared with the positive control group at the end of the trial. The female adult reduction was higher than the male reduction, most likely indicating the higher blood intake of the female worms [8]. Unfortunately, the reductions of adult worms were not statistically significant, probably due to the presence of nonresponsive animals in each group and the sampling size.…”
Section: Discussionmentioning
confidence: 85%
“…Until now, many native and recombinant proteins have been investigated in different immunization trials against H. contortus and most cases demonstrated variable reduction in fecal egg output and worm burdens [3,[6][7][8][9]. DNA vaccines have also been tested and showed partial protection against H. contortus [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several native and recombinant antigens have been tested in immunization trials against H. contortus and a variable degree of protection has been found in most cases . Similarly, different vaccination strategies have also been tested, including the use of different adjuvants or DNA vaccines .…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination of young goats did not sufficiently protect against H contortus infections on pasture. 12 For the production of this vaccine, the native antigens need to be extracted and purified locally from adult H contortus derived from infected sheep. A vaccine based on recombinantly expressed antigens would have advantages compared with a native antigen vaccine for reproducibility of product batches, biosafety, and global distribution.…”
Section: Haemonchus Contortusmentioning
confidence: 99%